PENERJEMAHAN DAJARE DALAM KOMIKKUROKO NO BASKET KARYA FUJIMAKI TADATOSHI - Chandra Sinta Dewi, Kadek Dwi (Humanis; Volume 15. No.3. Juni 2016, 2016)
The title of this study is “The Translation of Dajare in Kuroko no Basket Comic by Fujimaki Tadatoshi”. This study aims to find the form of dajare after being translated and to obtain details of procedures that occurred in dajare translation from Japanese to Indonesian. The theories used in this study are dajare translation strategy according to Delabastita (2004) and translation procedure according to Machali (2000). The data resource are comic by Fujimaki Tadatoshi entitled Kuroko no Basket volume one to ten. The data were analyzed with equivalent translation method and technique of sorting decisive element. The results of this study shows that from 26 data, five dataare translated into dajare, four of them are translated into near-homophonic dajare and one of them is translated into homophonic dajare. Furthermore, 17 data are translated into non-dajare forms and four data are not translated. Translation procedure that occur are transposition, modulation, and contextual matching. Transposition which occur are shape shifting type first, second and fourth. While modulation that occur are copulsive modulation and free modulation.
Keywords: translation, wordplay, dajare